Synthesis and Characterization of Bi13B0.48V0.49-xPxO21.45 and Efficient Catalyst for the Synthesis of 2,3-dihydroquinazolin-4(1H)-ones Derivatives Synthesis - Hanane Barebita; Youssef Merroun; Soumya Ferraa; Abderrazak Nimour; Abdelaziz Souizi; Taoufiq Guedira (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
A new compound has been found in the system Bi13B0.48V0.49-x PxO21.45 (with 0≤x≤0.34), were prepared by the direct solid-state reaction of Bi2O3, (NH4)2HPO4, V2O5, and B2O3. This material melts congruently and it crystallize with the sillenite structure (space group I23) and form a solid solution with the cubic lattice parameter increasing from with a = 10.1568 Å to 10.1436 Å with increasing of P2O5 molar. Consequently, the new composites belong to g-variety of solid state. The samples have been characterized by Fourier transform infrared spectroscopy (FT-IR), diffraction XRD and scanning electron microscopy (SEM) coupled to the EDX. On the other hand, the valorization of the prepared composites was performed by using them as heterogeneous catalyst in the 2,3-dihydroquinazolin-4(1H)-ones derivatives synthesis. The catalyst is stable (as a bench top catalyst) and reusable. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).